Social Interventions in the Family in the Post-COVID Pandemic Period - Pavlikova, Martina; Maturkanič, Patrik; Akimjak , Amantius; Mazur, Slawomir; Timor , Tsafi (Journal of Education Culture and Society, 2023)
Aim. The main aim of the authors of this study is to indicate the problem areas of individuals and the families during the pandemic and post-pandemic situation which occurred in connection with a deteriorating social and societal situation. Methods. Using a literary descriptive and deductive method, the authors identify, indicate and analyze not only epidemiological measures and the possibilities of applying social interventions in the individual and in the family, but also draw attention to state measures taken to manage new conditions of family life. Results. The analysis indicates a broad issue that affects individuals, families, and groups, as well as societal sectors. The authors point to the provision of interventions through social work, which takes into account the basic characteristics of the family. Social intervention therefore becomes an important tool in solving problematic situations of any small or large social group. Conclusions. The pandemic and post-pandemic situation brought about a number of problematic situations that had to be solved dynamically and, in many cases, through crisis intervention. Forms of assistance to individuals and families brought cohesion and unity, but also brought a number of other concerns reflecting the current adverse societal situation into the wider environment.